Genetic abnormalities in acute lymphoblastic leukemia - Pui, Ching Hon (Henry Stewart Talks, 2015)
Somatic genetic abnormalities, Genetic classification, Leukemogenesis, Heterogeneity due to age of presentation, differences in cooperative mutations and target cells undergoing malignant transformation, Genome-wide analysis disclosed novel genetic subtypes, driver mutations and targetable genetic lesions, Germline polymorphisms and mutations affecting cancer susceptibility, treatment response and toxicity, Precision medicine based on somatic and germline genetics